Analysis of risk factors affecting the postoperative drainage after a laparoscopic partial nephrectomy: a retrospective study - Tian, Yi-Qun; Ren, Xiang; Yin, Yi-Sheng; Wang, Jing; Li, Xing; Guo, Zi-Hao; Zeng, Xiao-Yong (Frontiers in Medicine, 2024)
Purpose:Laparoscopic partial nephrectomy (LPN) remains the most commonly used measure for treating localized renal cell cancer (RCC) with an increasing incidence of RCC ever since 1990s. This study aims to identify risk factors that affect postoperative time of drainage and total drainage volume after LPNs. Method: The clinical data of 612 RCC patients who received LPN from January 2012 to December 2022 in our hospital, including the postoperative time of drainage time and total drainage volume were retrospectively analyzed. Univariable, multivariable linear regression, and correlation analyses were used to identify the correlations between 21 factors, which includes gender, age, history of alcohol consumption, family history of RCC, body weight, body mass index (BMI), and operation tome, and the postoperative time of drainage time and total drainage volume. Results: The mean time of drainage was 3.52±0.71 days (range: 2 to 8 days), with an average total drainage volume of 259.83±72.64 mL (range: 50 to 620 mL). Both univariable and multivariable linear regression analyses revealed several statistically significant associations. Gender (p=0.04), age (p=0.008), smoking history (p<0.001), diabetes (p=0.032), operation time (p=0.014), and BMI (p=0.023) were identified as significant factors associated with the time of drainage. On the other hand, age (p=0.008), smoking history (p<0.001), diabetes (p=0.006), and BMI (p=0.016) emerged as independent risk factors influencing the total drainage volume. Conclusion:The duration of postoperative drainage was found to be associated with gender, age, smoking history, diabetes, operation time, and BMI. In contrast, the total drainage volume was primarily influenced by age, smoking history, diabetes, and high BMI following LPNs. For patients with these conditions, meticulous attention to hemostasis and bleeding control is crucial during the perioperative period.